FINANCIAL EDUCATION AS A DIGITAL MARKETING STRATEGY: THE CASE OF XP INC. AND HOLDINGS: the case of XP Inc. and holdings - Maroldi Barreiros, Talita; Mundo Neto, Martin (Revista Interface Tecnológica, 2022)
The objective of this research was to analyze the digital marketing strategies of the XP Inc group. It was considered the 4Cs marketing mix focusing on the “Communication” dimension, identifying the emphasis on Financial Education and the group's participation in four social networks: Instagram, Facebook, Youtube and LinkedIn. It is a case study of the XP Inc. group and its subsidiaries – XP Investimentos, Rico and Clear. The consulted data are in the public domain and were collected until September 2021, considering the different parameters of these media. The tabulated data indicated XP Investimentos as the company that most incorporates Communication in these media, as it is ahead of the others in the Publications and Followers – Instagram categories; Following and Likes – Facebook; Views – Youtube; Followers – LinkedIn. All of them publicize their financial products promoting Financial Education through exclusive platforms with financial courses, except for the broker Clear, which redirects the public to XP's XpeedSchool platform, but it is the only one that has a specific Financial Education playlist on the Youtube channel, the " EducaClear'.
Keywords: XP Investimentos; Financial Education; Digital Marketing; Platform Economy